Towards an expanded role of CAFGU active auxiliaries in counter-insurgency operations a policy paper - Baclor, Jovy L.; University of the Philippines Diliman National College of Public Administration and Governance (2003)
The present role of CAFGU Active Auxilliaries (CAA) is spelled-out in the Armed Forces of the Philippines Letter of Instruction TANGGOL-BAYAN (AFP LOI 07/87) that says, "CAAs should assist the local government authorities in the protection of life and property, security of vital facilities and public utilities, and the delivery of public safety services in their respective communities specially during local emergency situation." This is based on the provision in EO 264 (Providing for the Citizen Armed Force) that says,"CAAs shall be utilized primarily for the defense of their localities in support of AFP operations."Fifteen years since he CAFGU's inception, the role given to CAAs has not been changed nor expanded. In the wake of changes of the nature of war adopted by the local communists, as well as the different approaches currently pursued by the AFP directed against this threat group, it is but timely to look at the possibility of expanding the role of CAAs as employed by the AFP in counter-insurgency operation. As a matter of policy, this writer views that there is a need to review the role given to CAA in order for the latter to be directly utilized in CMO. Among the options the AFP may consider are the following: (1) To incorporate the CAA organization into the CMO doctrine of the AFP; 92) To employ/utilize all the present CAAs in the conduct of CMO; and, (3) To expand the present role of CAA so that they could be utilized also in CMO, particularly in directly confronting the non-combat activities of the LCM. This paper commends that the AFP should expand the present role of CAA. Rather than limit them to their present role, they should be given the clear mandate of confronting directly the non-combat activities of the insurgents, i.e. mass organization and mobilization, propaganda, recruitment and the like. They should be utilized in CMO such as in counter-organizing, psychological operations, public information, educational campaigns, community relations, civic actions, developmental works and the like. This would entail amending the provisions in the operational policy given to CAA as provided for in LOI 07/87 " TANGGOL BAYAN." If possible, the provision in EO 264 may also be amended. It is opined by this writer that the active involvement of CAAs in CMO would paved the way for the complete dismatling of the political infrastructures of the LCM leading to an early resolution of the communist insurgensy problem in the country.
"October 2003."
A policy paper (P.A. 247)
Keywords: Paramilitary forces -- Philippines; Counterinsurgency -- Philippines